Magnetic Properties of a Diluted Bi-Layer Borophene Structure: Monte Carlo Study. Issue 212 (21st November 2020) - Qajjour, M.; Fadil, Z.; Mhirech, A.; Kabouchi, B.; Bahmad, L.; Ousi Benomar, W.
Abstract: Using Monte Carlo simulations under the Metropolis algorithm, we study the dilution effect on the magnetic properties in a bi-layer borophene structure. The system is formed by two layers, where each layer contains two sub-lattices of 210 atoms (with mixed spins σ = 3/2 and S = 5/2). The ground-state phase diagrams are presented in different physical parameter planes. Besides, the thermal variation of the total and partial magnetizations and susceptibilities are reported by applying Monte Carlo method. Furthermore, the dilution effect of the S spins and/or σ spins is investigated. It is found that the dilution affects the magnetizations and the hysteresis loops of the studied system strongly.